China as a subject of the international tourist market - Lushchyk, Mariya; Vytrykush, Pavlo (Human Geography Journal, 2022)
Given the prospects for the development of the Chinese tourism market, we consider it appropriate to thoroughly study the impact of Chinese conditions on the global tourism industry and China’s international tourism positioning. Literary analysis of Chinese tourism research has shown a growing interest in this issue since the 2010s. Most scholars, tourism practitioners, government officials and professionals in tourism agencies agree that the Chinese tourism market has mega potential and high development dynamics. However, while scientific reviews of the past decade have focused exclusively on researching the travel geography of Chinese travelers and the dynamics of Chinese outbound tourism, modern work provides a deep understanding of Chinese tourists’ behavior and experiences and highlights negative aspects of Chinese mass tourism. In this article, the author specifies China’s place in the global tourism market, using quantitative data and tourism indices. In particular, after ranking the world countries on key quantitative indicators of the level of development of the tourism industry (number of tourists, number of international tourist arrivals, number of revenues from tourism), China’s strong position was revealed (3rd, 4th and 11th respectively).Graphs of changes in the number of international tourist arrivals and cash inflows from tourism showed a positive trend. In particular, in 2019 a record was reached among the number of tourists and the number of tourist arrivals in China for the entire research period. At the same time, it should be noted that the Covid-19 pandemic has not bypassed China’s tourism sector and in 2020 the number of international tourist arrivals decreased fivefold (this is the lowest figure for the country in the history of collecting international tourism statistics, since 1995). revenues from international tourists reached 14.2 billion dollars. (less than ever in the last 20 years). The prospects of the Chinese market and optimistic dynamics of its development were evidenced by the highest rating indices in the field of tourism and travel − Travel & Tourism Competitiveness Index (2019) and Travel & Tourism Development Index (2021), where China ranked 13th and 12th respectively. Thus, quantitative indicators and integrated indices have confirmed China’s important position in the tourism market and allow us to predict their stable strengthening and China’s short-term world leadership in the tourism sector.